VD_FINDINFO MP / 2022 / 1 vom 8. April 2022 - VD Tribunal cantonal (2022)
NOVA, PROTECTION DES MARQUES, CONCURRENCE DÉLOYALE, RISQUE DE CONFUSION | 29 CC, 956 al. 2 CO, 3 al. 1 let. b LCD, 3 al. 1 let. d LCD, 3 al. 1 let. e LCD, 4 let. a LCD, 5 LCD, 264 CPC (CH), 267 CPC (CH), 90 CPC (CH)